ChemInform Abstract: A Trifluoroacetic Acid Catalyzed Domino Reaction as an Approach to Amino Acid Derived 2, 3‐Dihydro‐1H‐1, 5‐benzodiazepines. Issue 46 (18th November 2014) - Bera, Saurav; Kandiyal, Pancham S.; Ampapathi, Ravi S.; Panda, Gautam
Abstract The strategy allows the preparation of a library of benzodiazepines with potential pharmaceutical and biological activity.